Effect of laboratory aging on the stiffness and fatigue cracking of asphalt mixture containing bamboo fiber. (20th January 2022) - Jia, Haichuan; Chen, Huaxin; Sheng, Yanping; Meng, Jiandang; Cui, Shian; Kim, Y. Richard; Huang, Shouchao; Qin, Hao
Abstract: Bamboo fiber is a kind of environmentally friendly fiber, which exhibits low pollution, biodegradable, and renewable characteristics. Thus, bamboo fiber as a natural fiber used to replace other synthetic fibers in asphalt mixtures can not only enhance the road performance of the asphalt mixture, but also save resources and reduce environmental pollution. Fiber-reinforced asphalt mixture can enhance the cracking resistance performance of asphalt pavement in long-term service life. In this study, the stiffness and fatigue performance of fiber-reinforced asphalt mixture (bamboo fiber and polyester fiber) subjected to different aging conditions were investigated. Short-term aging and long-term aging procedure were carried out in accordance with AASHTO R30 and the NCHRP 09–54 project research (0, 4, and 7 days of treatment at 95 °C), respectively. Dynamic modulus and uniaxial fatigue tests were then performed to investigate the stiffness and cracking properties of specimens after different aging durations. Finally, the viscoelastic characterization and fatigue life were analyzed with the simplified viscoelastic continuum damage (S-VECD) theory. The test results indicated that the dynamic modulus values of the asphalt mixtures increased with aging levels and the observed difference after aging in the modulus of fiber-reinforced asphalt mixture is more noticeable. Furthermore, fiber addition increased the dynamic modulus values of the asphalt mixture, and the modulus change trend of bamboo fiber asphalt mixture (BAM) was similar to that of polyester fiber asphalt mixture (PAM). The fatigue life of the asphalt mixture decreased with an increase in aging levels, but the inclusion of fiber enhanced the fatigue resistance performance compared with hot mix asphalt (HMA). BAM exhibits stiffness and cracking performances similar to PAM after long-term aging. Hence, the renewable bamboo fiber could be used as a viable alternative fiber in the asphalt mixture to enhance the fatigue life of the asphalt mixture and realize green development.